Understanding the impact of non-synchronous wind and solar generation on grid stability and identifying mitigation pathways. (15th March 2020) - Johnson, Samuel C.; Rhodes, Joshua D.; Webber, Michael E.
Highlights: Low system inertia could prevent a 100% penetration of non-synchronous generation. Changing grid operating practices could enable higher renewable energy penetrations. Retiring nuclear plants might allow lower system inertia, but increase emissions. Fast frequency response could also allow reduced inertia, but is less impactful. Inertia prices might exceed the market cap at high renewable energy penetrations. Abstract: High penetrations of non-synchronous renewable energy generation can decrease overall grid stability because these units do not provide rotational inertia in the same way as traditional synchronously-connected generators. Many recent studies have investigated 100% renewable energy generation scenarios, but few have explored the trade-offs associated with an electricity grid dominated by non-synchronous generation (i.e. wind and solar). Fast frequency response from grid-forming inverters—along with other technology changes—could help mitigate low system inertia levels, but the impact of this response is unknown. An inertia-constrained unit commitment and dispatch model was used to study the stability of future grid scenarios with high penetrations of non-synchronous renewable energy generation under a variety of technology scenarios. The Texas grid (the Electric Reliability Council of Texas – ERCOT) was used as a test case and instances when the system inertia fell below 100 GW · s (the grid's current minimum level) were recorded. When the modeled critical inertia limit was reduced to 80 GW · s to represent changes in grid operation, no critical inertia hours occurred for renewable energy penetrations up to 93% of annual energy. The critical inertia limit could drop to 60 GW · s if the largest generators in ERCOT (two co-located nuclear plants) were retired, but emissions increased by 25% in these scenarios. If the critical inertia limit was kept the same (100 GW · s), adding 525 MW of fast frequency response from wind, solar, and energy storage could reduce the number of critical inertia hours by up to 95%. These results show that changes to grid operating practices and generator retirements reduced critical inertia hours more than fast frequency response from inverter-connected resources. Each of these mitigation pathways has associated trade-offs, so the transition to a grid dominated by non-synchronous energy generation should be handled with care, but high renewable energy penetrations (i.e. > 80%) might be feasible in Texas.